Construction Noise Measurement On The Earthmoving Activities - Lim, Ryan Jun Min (2020)
The noise that is introduced in the workplace which is experienced by the employees is termed as occupational noise. Construction noise is the occupational noise for the construction industry and the main contribution of noise is originated from the earth-moving machines. The major concern about occupational noise is its negative impacts towards worker’s health and safety. Some of these impacts include noise-induced hearing loss, tinnitus, and workrelated accidents. It has been discovered that the cases of occupational noiseinduced hearing impairment are rising in Malaysia, yet the implementation of noise control is rarely seen and been neglected in the construction industry. Thus, this final year project executed the noise measurement on the earthmoving activities for two construction sites in Malaysia. The primary aim of this study is to investigate the current noise exposure problem produced by earth-moving activities in Malaysia’s construction project. The objectives of this project were to measure the boundary noise level of earth-moving activities, to measure the personal noise exposure level of the operator during earth-moving activities, and to propose appropriate noise control methods for reducing the noise exposure level from the earth-moving activities. Field measurements were carried out in two construction sites in Kuala Lumpur, Malaysia, namely Tria 9 Seputeh and Zhong Ji Sentul. A total of three case studies which consists of seven different boundary points were conducted for the measurement of boundary noise level. Another three sets of personal noise exposure level measurements had been executed on the operators from different earth-moving machines. The results showed that the equivalent sound level exceeded the permissible sound level and action level of 85 dBA respectively for all the boundary points, where some of the points are located near to the critical position like residential area and school. All the results obtained from the personal noise exposure level do not exceed the permissible exposure limit of 90 dBA. Permanent and temporary noise barriers as well as the application of hearing protection devices are selected and proposed to the workers and operators. In conclusion, the results of this research project can be disseminated to construction workers in order to raise their risk awareness regarding to the noise exposure issue at the workplace.